Local anaesthetic transperineal (LATP) prostate biopsy using a probe‐mounted transperineal access system: a multicentre prospective outcome analysis. (12th April 2021) - Lopez, J. Francisco; Campbell, Angus; Omer, Altan; Stroman, Luke; Bondad, Jasper; Austin, Tom; Reeves, Thomas; Phelan, Curtis; Leiblich, Aaron; Philippou, Yiannis; Lovegrove, Catherine E.; Ranasinha, Nithesh; et al.
Abstract : Objectives: To assess the feasibility of local anaesthetic transperineal (LATP) technique using a single‐freehand transperineal (TP) access device, and report initial prostate cancer (PCa) detection, infection rates, and tolerability. Patients and methods: Observational study of a multicentre prospective cohort, including all consecutive cases. LATP was performed in three settings: (i) first biopsy in suspected PCa, (ii) confirmatory biopsies for active surveillance, and (iii) repeat biopsy in suspected PCa. All patients received pre‐procedure antibiotics according to local hospital guidelines. Local anaesthesia was achieved by perineal skin infiltration and periprostatic nerve block without sedation. Ginsburg protocol principles were followed for systematic biopsies including cognitive magnetic resonance imaging‐targeted biopsies when needed using the PrecisionPoint™ TP access device. Procedure‐related complications and oncological outcomes were prospectively and consecutively collected. A validated questionnaire was used in a subset of centres to collect data on patient‐reported outcome measures (PROMs). Results: Some 1218 patients underwent LATP biopsies at 10 centres: 55%, 24%, and 21% for each of the three settings, respectively. Any grade PCa was diagnosed in 816 patients (67%), of which 634 (52% of total) had clinically significant disease. Two cases of sepsis were documented (0.16%) and urinary retention was observed in 19 patients (1.6%). PROMs were distributed to 419 patients, with a 56% response rate ( n  = 234). In these men, pain during the biopsy was described as either 'not at all' or 'a little' painful by 64% of patients. Haematuria was the most common reported symptom (77%). When exploring attitude to re‐biopsy, 48% said it would be 'not a problem' and in contrast 8.1% would consider it a 'major problem'. Most of the patients (81%) described the biopsy as a 'minor or moderate procedure tolerable under local anaesthesia', while 5.6% perceived it as a 'major procedure that requires general anaesthesia'. Conclusion: Our data suggest that LATP biopsy using a TP access system mounted to the ultrasound probe achieves excellent PCa detection, with a very low sepsis rate, and is safe and well tolerated. We believe a randomised controlled trial comparing LATP with transrectal ultrasound‐guided biopsy (TRUS) to investigate the relative trade‐offs between each biopsy technique would be helpful.